2019
DOI: 10.18632/aging.102179
|View full text |Cite
|
Sign up to set email alerts
|

PU-91 drug rescues human age-related macular degeneration RPE cells; implications for AMD therapeutics

Abstract: Since mitochondrial dysfunction is implicated in the pathogenesis of AMD, this study is based on the premise that repurposing of mitochondria-stabilizing FDA-approved drugs such as PU-91, might rescue AMD RPE cells from AMD mitochondria-induced damage. The PU-91 drug upregulates PGC-1α which is a critical regulator of mitochondrial biogenesis. Herein, we tested the therapeutic potential of PU-91 drug and examined the additive effects of treatment with PU-91 and esterase inhibitors i.e., EI-12 and EI-78, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…All AMD patients used in this study have been clinically characterized, and genetic and clinical information of all patients is available as partly mentioned in Table 1. Morphological and functional evaluation of these AMD RPE transmitochondrial cell lines in our previous studies revealed significant mitochondrial and cellular damage as evidenced by apoptotic cell death, higher oxidative stress, low antioxidant content, lower numbers of mitochondria, and higher mtDNA fragmentation in AMD RPE cells [9][10][11][12][13]. Therefore, AMD RPE transmitochondrial cell lines serve as a good in vitro model to test the effects of resveratrol as a potential over-the-counter candidate for AMD therapy.…”
Section: Discussionmentioning
confidence: 94%
“…All AMD patients used in this study have been clinically characterized, and genetic and clinical information of all patients is available as partly mentioned in Table 1. Morphological and functional evaluation of these AMD RPE transmitochondrial cell lines in our previous studies revealed significant mitochondrial and cellular damage as evidenced by apoptotic cell death, higher oxidative stress, low antioxidant content, lower numbers of mitochondria, and higher mtDNA fragmentation in AMD RPE cells [9][10][11][12][13]. Therefore, AMD RPE transmitochondrial cell lines serve as a good in vitro model to test the effects of resveratrol as a potential over-the-counter candidate for AMD therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Given the anti-inflammatory, antioxidant, and proautophagic activities of zinc, dietary supplementation may be hypothesized as a valuable tool in AMD prevention. Dedicated studies have reported that zinc supplementation in combination with the AREDS formula has the potential to slow AMD progression, while a higher intake of dietary zinc has beneficial effects on AMD incidence [450][451][452][453] [454]. The same research group expanded their investigation, revealing varied responses to PU-91 drug treatment among AMD cybrids with different mtDNA haplogroups [455].…”
Section: Autophagy Enhancersmentioning
confidence: 99%
“…Therefore, drugs that activate mitophagy in RPE cells could provide a novel therapeutic strategy for AMD. Recently, numerous mitophagy modulators that either activate or inhibit mitophagy, including AICAR (5aminoimidazole-4-carboxamide ribonucleotide), an AMP analogue that maintains the optimal function of mitochondria (Ebeling et al, 2022), PGC-1α (an important regulator of mitochondrial biosynthesis) (Hyttinen et al, 2021), human retinal progenitor cells (hRPCs) (Yu et al, 2021), the mitochondria-targeted antioxidant triphenylphosphine (TPP)nicotinic acid (Kim et al, 2021), melatonin (Mehrzadi et al, 2020), the mitochondrial activator PU-91 (Nashine et al, 2019), the mitochondria-derived peptide variant Humanin G (HNG) (Nashine et al, 2017), and the mitochondria-targeted antioxidant SkQ1 (Telegina et al, 2020;Fisher et al, 2022), have been discovered. mtDNA repair could be another target for improving mitochondrial function.…”
Section: Mitophagy Mediated By Ampkmentioning
confidence: 99%